Arabidopsis thaliana zinc accumulation in leaf trichomes is correlated with zinc concentration in leaves - Ricachenevsky, Felipe K. (Sci Rep, 2021)
Zinc (Zn) is a key micronutrient for plants and animals, and understanding Zn homeostasis in plants can improve both agriculture and human health. While root Zn transporters in plant model species have been characterized in detail, comparatively little is known about shoot processes controlling Zn concentrations and spatial distribution. Previous work showed that Zn hyperaccumulator species such as Arabidopsis halleri accumulate Zn and other metals in leaf trichomes. To date there is no systematic study regarding Zn accumulation in the trichomes of the non-accumulating, genetic model species A. thaliana. Here, we used Synchrotron X-Ray Fluorescence mapping to show that Zn accumulates at the base of trichomes of A. thaliana. Using transgenic and natural accessions of A thaliana that vary in bulk leaf Zn concentration, we demonstrate that higher leaf Zn increases total Zn found at the base of trichome cells. Our data indicates that Zn accumulation in trichomes is a function of the Zn status of the plant, and provides the basis for future studies on a genetically tractable plant species to understand the molecular steps involved in Zn spatial distribution in leaves.